THE ADSORBER COMPONENT ADDITION IN CHEMCAD SOFTWARE FOR HELIUM PURIFICATION MODELLING AND SIMULATION - Sriyono Sriyono (BATAN, 2018)
THE ADSORBER COMPONENT ADDITION IN CHEMCAD SOFTWARE FOR HELIUM PURIFICATION MODELLING AND SIMULATION. Helium purification system (HPS) is an important system in RDE. This system removed dust particles and gas impurities in primary coolant of RDE. The impurities are dust carbon, N2, O2, H2, O2, CH4, CO, and CO2. One of the components which required in HPS is an adsorber. In ChemCAD software palette, adsorber component is not yet available and should be added. This paper discussed the adsorber component addition in ChemCAD. The addition is made by using Excel icon facility, while coding is made by using Visual Basic. The purpose of adding adsorber component to ChemCAD palette is it can be used for helium purification modeling. The adsorption process principle used in adsorber modeling is Langmuir method. After finishing the coding, adsorber component will be integrated into ChemCAD. This component then used for modeling and simulated the helium purification of primary coolant of RDE especially for oxygen adsorption. The simulation results are compared to SuperPro Designer modeled which is also demonstrated the same problem. The differences results of adsorber component simulation between ChemCAD and SuperPro Designer did not more than 0.02%. It can be concluded that the adsorber component which is added to the ChemCAD is valid so it can be used to simulate the helium purification system in RDE.